Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Kesadaran Sejarah Siswa dalam Pembelajaran Sejarah - Hafidz Zachary; Nana Supriatna; Didin Saripudin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study originates from fundamental issues identified in the History learning process at SMK Mahardhika, where the teaching activities predominantly rely on conventional methods, such as textual material delivery, monotonous narration, and rote memorization without deep comprehension. Through the identification of these issues, it was revealed that the core challenge lies in implementing differentiated learning strategies to enhance students' historical awareness in class XI RPL 1 at SMK Mahardhika.The objective of this research is to formulate an effective approach to fostering historical awareness through more dynamic and adaptive methods. The approach employed is classroom action research, which enables continuous development and evaluation of methods within the learning context. The findings of the study reveal several significant points. First, the instructional design was prepared adequately, although there were some discrepancies and challenges during the initial implementation phase. Second, the educators successfully executed the learning process in alignment with the planned design, particularly in applying differentiated learning strategies. This indicates that such strategies hold considerable potential in creating more meaningful and contextualized learning experiences for students.Third, the increase in understanding of historical awareness has been successfully increased because it is assisted by differentiated learning based on content. Fourth, the obstacles faced by partner teachers, the most important form of assignments that are less popular, but are overcome by differentiation of learning style content. Differentiated learning is one alternative in learning strategies because it can accommodate various needs or characteristics of students in classroom learning.